The use of self-administered questionaires about food habits. - Jacobsen, Bjarne Koster (Universitetet i Tromsø, 1988)
Papers in this thesis: I: Jacobsen BK, Thelle DS.: ‘The Tromsø Heart Study: responders and non-responders to a health questionnaire, do they differ?’, manuscript, later published in: Scand J Soc Med. 1988;16(2):101-4 II: Bjarne K. Jacobsen, Synnøve F. Knutsen, and Raymond Kriutsen: ‘The Tromsø Heart Study: Comparison of Information from a Short Food Frequency Questionnaire with a Dietary History Survey’, Scand J Public Health, March 1987 15: 41-47 III: Jacobsen BK, Thelle DS: ‘THE TROMSØ HEART STUDY: FOOD HABITS, SERUM TOTAL CHOLESTEROL, HDL CHOLESTEROL, AND TRIGLYCERIDES’. Am. J. Epidemiol. (1987) 125 (4): 622-630 IV: Bjarne K. Jacobsen, Dag S. Thelle: ‘The Tromsø heart study: The relationship between food habits and the body mass index’. Journal of Chronic Diseases, Volume 40, Issue 8, 1987, Pages 795–800 ( http://dx.doi.org/10.1016/0021-9681(87)90131-7 ) V: Bjarne Koster Jacobsen and Dag Steinar Thelle: ‘The Tromsø Heart Study: Is Coffee Drinking an Indicator of a Life Style with High Risk for Ischemic Heart Disease?’. Acta Medica Scandinavica, 1987, Volume 222, Issue 3, pages 215–221 ( http://dx.doi.org/10.1111/j.0954-6820.1987.tb10662.x ) VI: Bjarne K. Jacobsen and Dag S. Thelle: ‘RISK FACTORS FOR CORONARY HEART DISEASE AND LEVEL OF EDUCATION: THE TROMSØ HEART STUDY’. Published in Am. J. Epidemiol. (1988) 127 (5): 923-932. VII: Bjarne K. Jacobsen, Erik Bjelke, Gunnar Kvåle, and Ivar Heuch: ‘Coffee Drinking, Mortality, and Cancer Incidence: Results From a Norwegian Prospective Study’. Published in JNCI J Natl Cancer Inst (1986) 76 (5): 823-831.